2009
DOI: 10.1002/app.30584
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and tensile properties of Borassus fruit fibers

Abstract: The chemical and instrumental analysis of alkali-treated Borassus fibers is carried out to explore the possibility of their use as reinforcement in green composites. The chemical analysis shows presence of a-cellulose, hemicellulose, and lignin. This is further confirmed by FTIR and high-resolution solid-state 13 C NMR spectroscopy. The influence of alkali treatment on morphology and mechanical properties is attempted by SEM and UTM techniques, respectively. The wide-angle X-ray dif-fraction analysis of the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(70 citation statements)
references
References 33 publications
4
65
0
Order By: Relevance
“…The diffraction peaks observed around 2θ of 16° correspond to the diffraction of the plan (110) and represent amorphous cellulose.The diffraction peaks at 2θ of 22° and 34° correspond respectively to diffractions of the plans (002) and (004) and are attributed to the crystalline shape of the cellulose [19]. However, we note the presence of a peak of low intensity at 2θ=11.36° due to traces of Hémicellulose or lignin.…”
Section: Figure 1: Xrd Plot Of Various Samples A) Ht3 and Ht2; B) Extmentioning
confidence: 66%
See 1 more Smart Citation
“…The diffraction peaks observed around 2θ of 16° correspond to the diffraction of the plan (110) and represent amorphous cellulose.The diffraction peaks at 2θ of 22° and 34° correspond respectively to diffractions of the plans (002) and (004) and are attributed to the crystalline shape of the cellulose [19]. However, we note the presence of a peak of low intensity at 2θ=11.36° due to traces of Hémicellulose or lignin.…”
Section: Figure 1: Xrd Plot Of Various Samples A) Ht3 and Ht2; B) Extmentioning
confidence: 66%
“…The IR spectrum of extracted cellulose is represented in figure 2b.It shows the characteristic bands of cellulose.The bands located towards 3400 and 2900 cm -1 correspond respectively to the stretching of O-H and C-H group of the cellulose [19]. A band at 1636 cm -1 is attributed to adsorbed water.The 1370 cm -1 band reflects the asymmetrical deformation of C-H of cellulose [20].…”
Section: Study By Ir Spectroscopymentioning
confidence: 97%
“…It is supposed that a rise in crystallinity index is due to the extraction of amorphous lignin loosely attached to the cellulose fibre. The same cannot be said for NaOH pre-treated flours, though alkali treatment is known for increasing CI as observed by other researchers [24] and [25] who found that realignment of cellulose molecules due to loss of amorphous lignin and hemicellulose resulted in an increase of crystallinity. However, 1% and 5 %NaOH+Laccase treated flours have lower crystallinity index than untreated.…”
Section: A X-ray Diffractometer Analysismentioning
confidence: 89%
“…For lignin, absorption bands at 1593, 1512, 1450 and 1033 cm -1 relate to C=C stretching, C-O stretching, -CH 3 asymmetric and aromatic -CH in plane deformation respectively. For hemicelluloses, the absorption bands focused at 1735 and 1228 are assigned to C=O carbonyl stretching and C-O-C stretching vibrations of ester groups [25]. The absorption bands at 1600-1650 cm -1 correspond to bending of absorbed water molecules.…”
Section: A X-ray Diffractometer Analysismentioning
confidence: 99%
“…Since hemicellulose degrades more rapidly than cellulose, thermal analysis of hemicellulose-extracted hemp fibers confirmed improved thermal stability [186]. The decrease in the content of hemicellulose resulted in increased Young's modulus and elongation at break for alkali-treated Borassus fruit fibers [187]. Moreover, hot-water-pretreated wood flakes showed a decrease in wettability consistent with a decrease in the hydrophilic character of wood strands.…”
Section: Hemicellulosic Polysaccharidesmentioning
confidence: 99%